UHPLC-ESI-QTOF-MS/MS characterization, antioxidant and antidiabetic properties of sorghum grains. (1st February 2021) - Ofosu, Fred Kwame; Elahi, Fazle; Daliri, Eric Banan-Mwine; Tyagi, Akanksha; Chen, Xiu Qin; Chelliah, Ramachandran; Kim, Joong-Hark; Han, Sang-Ik; Oh, Deog-Hwan
Highlights: Investigated sorghum grains exhibited strong antioxidant capacity. Soluble phenolics showed potent inhibition of α-glucosidase and α-amylase. Flavonoid rich phenolics demonstrated strong anti-glycation properties. Phenolic compounds were predominantly flavonoids mainly flavones, isoflavones and dihydroflavonols. Investigated sorghum grains have potential antidiabetic activities. Abstract: The phenolic compounds composition, antioxidant and antidiabetic properties of eight brown sorghum genotypes were investigated. DPPH radical scavenging activity was highest in SOR 03, followed by SOR 11, SOR 08 and SOR 33. SOR 33, SOR 03, SOR 08, SOR 11 showed the highest ABTS radical scavenging activity. Furthermore, SOR 11, SOR 17 and SOR 33 exhibited significantly higher percentage inhibitory activity of α-glucosidase and α-amylase (IC50  = 14.71, 32.98, 24.93 µg/ml and 27.6, 23.84, 45.01 µg/ml, respectively) compared to acarbose (IC50  = 59.34 and 27.73 µg/ml, respectively). Similarly, SOR 17, SOR 11 and SOR 33 showed significantly potent inhibition of AGEs formation with IC50 values of 14.19, 18.23 and 26.31 µg/ml, respectively, compared to aminoguanidine (AG) (52.30 µg/ml). Flavones, isoflavones and dihydroflavonols were the predominant flavonoids identified in SOR 11, SOR 17 and SOR 33 genotypes. Therefore, these sorghum grains are potential candidates for the development of functional foods.